Network reconfiguration for load balancing in distribution networks - M.A. Kashem; Ganapathy, V.; Jasmon, G.B. (1999)
Network reconfiguration of a power distribution system is an operation to alter the topological structure of distribution feeders by changing open/closed status of sectionalising and tie switches. By transferring loads from the heavily loaded feeders to the lightly loaded ones, network reconfiguration can balance feeder loads and alleviate overload conditions of a network. The branch load-balancing index and the overall system load-balancing index are used to determine the loading conditions of the system and maximum system loading capacity. The index value has to be minimum in the optimal configuration of load balancing. For optimal load balancing condition the branch load-balancing indices in the network are to be more or less equal, and also approximately equal to the system load-balancing index. A general formulation of the network reconfiguration for load balancing is given for the optimal balancing of loads in distribution network and a solution approach is presented. The solution employs a search over different radial configurations, created by considering branch-exchange type switches. The proposed algorithm, called distance measurement technique (DMT) has been developed based on the two-stage solution methodology. The first stage finds a loop, which gives the maximum improvement in load balancing in the network. In the second stage, a switching option is determined in that loop to obtain maximum improvement in load balancing. The DMT employs a graphical method in which different circles are drawn and the distances of various points from the centre of the loop circle are computed to achieve the optimal or near optimal configuration for load balancing. The solution algorithm of the proposed method can identify the most effective branch-exchange operations for load balancing with minimum computational effort. The algorithm has been tested with promising results on a 69-bus radial distribution system.